2020
DOI: 10.1177/1358863x20970263
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hospital volume on outcomes in patients with acute pulmonary embolism: Analysis of a 70,000 patient database

Abstract: Positive relationships between volume and outcome have been seen in several surgical and medical conditions, resulting in more centralized and specialized care structures. Currently, there is a scarcity of literature involving the volume–outcome relationship in pulmonary embolism (PE). Using a state-wide dataset that encapsulates all non-federal admissions in New York State, we performed a retrospective cohort study on admitted patients with a diagnosis of PE. A total of 70,443 cases were separated into volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…17,18,21 However, such data in PE is only recently emerging. 14 The decision to transfer may broadly depend on either PE-specific scenarios (ie, clot-in-transit, high bleeding risk, PE in pregnancy, comorbid medical illnesses) or transferring facility capabilities (ie, ability to offer advanced reperfusion therapies, capability to manage post-thrombolysis bleeding complications, and availability of cardiac surgery and critically trained support staff). Table 3 lists the factors to review when IHT is being considered.…”
Section: Needs For Advanced Management For Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,21 However, such data in PE is only recently emerging. 14 The decision to transfer may broadly depend on either PE-specific scenarios (ie, clot-in-transit, high bleeding risk, PE in pregnancy, comorbid medical illnesses) or transferring facility capabilities (ie, ability to offer advanced reperfusion therapies, capability to manage post-thrombolysis bleeding complications, and availability of cardiac surgery and critically trained support staff). Table 3 lists the factors to review when IHT is being considered.…”
Section: Needs For Advanced Management For Transfermentioning
confidence: 99%
“…10 Data from large-scale multisite observational cohorts suggest that patients with acute PE benefit (ie, short-term 30-day mortality) when treated at high-volume centers and by experienced physicians. [11][12][13][14] The recent European Society of Cardiology (ESC) guidelines for the diagnosis and management of acute PE highlights the value of PERTs for high-and intermediate-risk PEs. 15 One of the main challenges in treating these patients is the lack of access to locoregional expert PERT centers.…”
mentioning
confidence: 99%
“…Recent studies have revealed that there may be an association with better outcomes (lower cost, length of stay, readmission rates, and mortality) for patients with PE who are treated at high‐volume centers 17,18 . This leads us to believe that similar outcomes for RHT are likely to be improved if patients are treated at more experienced, higher‐volume centers, and transfer to a high‐volume center with expertise of RHT should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that there may be an association with better outcomes (lower cost, length of stay, readmission rates, and mortality) for patients with PE who are treated at high-volume centers. 17,18 This leads us to believe that similar outcomes for RHT are likely to be improved if patients are treated at more experienced, highervolume centers, and transfer to a high-volume center with expertise of RHT should be considered. It is advantageous to have experience with multiple treatment modalities across different specialties, an understanding of what treatment options are available at an institution and how to transfer these high-risk patients to a higher level of care if needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this edition of Vascular Medicine , Finkelstein and colleagues performed an observational analysis of the New York Statewide Planning and Research Cooperative System (SPARCS) database focused on PE admissions between 2009 and 2015. 4 They stratified hospitals according to low (< 52 cases/year), medium (52–87 cases/year), high (88–147 cases/year), and very high (> 148 cases/year) inpatient PE volumes. Using multivariable regression modeling accounting for demographic and illness severity variables among these four cohorts of PE volume, the investigators assessed length of stay, 30-day or PE-related readmission, 1-year all-cause mortality, and total charges.…”
mentioning
confidence: 99%